2002
DOI: 10.1046/j.1537-2995.2002.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Seven‐day storage of single‐donor platelets: recovery and survival in an autologous transfusion study

Abstract: Although declines in recovery and survival were noted, these are less than used previously to gain licensure of 7-day storage and are unlikely to be clinically significant. Extension of storage to 7 days could be implemented with bacterial screening methods to select out contaminated components without a significant effect on the platelet efficacy compared to 5-day components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
148
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(170 citation statements)
references
References 22 publications
22
148
0
Order By: Relevance
“…Several studies have showed that high levels of platelet activation may be related to a low survival potential for transfused platelets (3,4,19,20). However, Cardigan et al (21) reported that the reactivity of platelets to stimuli such as physiological agonists, rather than the glycoprotein expression without agonists, might be a better predictor of in vivo platelet transfusion efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that high levels of platelet activation may be related to a low survival potential for transfused platelets (3,4,19,20). However, Cardigan et al (21) reported that the reactivity of platelets to stimuli such as physiological agonists, rather than the glycoprotein expression without agonists, might be a better predictor of in vivo platelet transfusion efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Within the United States, premarket multicenter studies (or possibly postmarket studies) are currently under discussion to provide data that may allow the extension of storage to 7 days. It would be expected that the cost of culturing would be mitigated by the savings obtained by the extension of platelet storage time (20). For example, in Denmark, when bacterial culture was implemented in 1997, it was anticipated to be cost neutral if the outdating could be reduced from 18 to 8% by extending the storage time to 7 days (24).…”
Section: The Prospect Of Seven-day Storage With Detectionmentioning
confidence: 99%
“…Day 5 platelets were found to have a mean recovery of 63% and a mean survival of 160.8 hours, compared with day 7 platelets, which had a recovery and survival of 53.9% and 133.6 hours, respectively. 30 Numerous morphologic, biochemical and functional derangements occur during platelet storage. Platelets continue to be metabolically active at room temperature.…”
Section: Rapid Tests For Bacteriamentioning
confidence: 99%